Cardiovascular Outcomes of Romosozumab and Protective Role of Alendronate: A Conundrum or Clarification. Issue 7 (July 2019) - Asadipooya, Kamyar; Weinstock, Ada
Abstract : Osteoporosis and cardiovascular diseases are major public health issues. Bone and cardiovascular remodeling share multiple biological markers and pathways. Medical intervention, such as using romosozumab, an antisclerostin antibody, improves the clinical outcome of osteoporosis. However, blocking sclerostin leads to Wnt (wingless/integrated) activation and participation in the cardiovascular remodeling process, which could potentially lead to adverse events. Based on the opposing roles of bisphosphonates and the Wnt pathway on endothelial dysfunction, lipid accumulation and calcification of the vessel walls, the combination of romosozumab and bisphosphonates could be a new therapeutic approach to reducing the risks of adverse cardiovascular events in romosozumab receivers.